Stem cells from human exfoliated deciduous teeth relieves Alzheimer’s disease symptoms in SAMP8 mice by up-regulating the PPARγ pathway - Zhang, Xiaoshuang; Lei, Tong; Wang, Donghui; Cai, Shanglin; Hang, Zhongci; Yang, Yanjie; Bi, Wangyu; Xiao, Zhuangzhuang; Du, Hongwu (Biomedicine & pharmacotherapy, 2022)
The pathology of Alzheimer's disease (AD) is complex and heterogeneous, and there are currently no drugs that can stop its progression. The failure of traditional chemical small-molecule drug development showed the weakness of single target and made researchers look to cell therapy with multiple regulatory effects. Stem cells from human exfoliated deciduous teeth (SHED) are a kind of neural crest-derived mesenchymal stem cells which have broad prospects in the treatment of neurodegenerative diseases. In this study, we demonstrated the therapeutic effects of SHED in AD mice, including behavioral improvement, neuronal protection, and alleviation of neuroinflammation. Tracking experiments on SHED showed that some of the transplanted cells could enter the brain. To elucidate the role played by the majority of cells transplanted into veins, blood proteomic assays were performed. Data are available via ProteomeXchange with identifier PXD030313. Among the altered proteins, the PPAR pathway related to energy metabolism was considered to be an important signaling pathway involved in regulation through gene ontology analysis and pathway analysis. Western blot showed that the transplantation of SHED improved the glucose metabolism in AD mice by increasing the PPARγ signaling pathway. These results suggested that SHED have a potential in relieving AD pathological symptoms and improving behavioral cognition. The therapeutic mechanism of SHED is related to up-regulating PPARγ signaling pathway and reducing neuronal damage. [Display omitted] •Stem cells from human exfoliated deciduous teeth (SHED) effectively improved pathological indicators and improved spatial memory in AD mice.•By transferring GFP gene to track SHED in AD mice, the results showed that some cells penetrate the blood-brain barrier and enter the brain.•Blood proteome analysis showed that the transplantation of SHED changed the protein expression of AD mice, and the changed protein was related to the PPARγ pathway.•WB validation indicated that the PPARγ pathway may be a potential target for the treatment of AD.